Finite element analysis of warehouse steel structure using ansys - Muhammad Shafiq, Noor Zammizi (2017)
Frame is one of the important elements of this structure. Unfit or improper design can lead to the failure of a structure. The warehouse steel frame was analyzed by manual calculation and also design in ANSYS software. There are several methods can be used to analyses the behavior of steel warehouse frame. However, among all these methods, finite element method and probabilistic method will be a very effective method to obtain the strength and behavior of steel structure. This analysis is to determine the behavior of frame design for the warehouse structure. This research will mainly focus on the steel frame of warehouse structure. The yield strength of steel jacket that used is 500 N/